The Relationship of Delivery Method and Family Planning History with Via Examination Results (Visual Inspection of Acetic Acid)” - Rohmawati, Indah; Widyawati, Evita; Oktaviana, Friska; Fitriani, Evi Tunjung (GLOBAL HEALTH SCIENCE GROUP, 2024)
VIA (Visual Acetic Acid Inspection) is a type of examination to detect cervical cancer. There are several factors that can cause positive VIA results and every couple of childbearing age (PUS) should carry out early detection of cervical cancer once a year, one of which is through an VIA examination. However, unfortunately there are still many couples of childbearing age who have not done so and when the examination is carried out, some of the results are positive and are even in an advanced stage. The Objective of this study was to determine the relationship between delivery method and birth control history with the results of VIA examination (visual inspection of acetic acid). This type of observational analytic research, cross-sectional design. The research population was all couple of childbearing age (PUS) in Malang Regency. The inclusion criteria were carrying out a VIA examination at the Polowijen Malang Community Health Center and having given birth. The sample consisted of 34 respondents. The research was carried out on November 8 2023. Data was collected by conducting interviews about birth methods and family planning history as well as conducting VIA examinations. Data were analyzed using the chi-square test. There is no relationship between the method of delivery and the results of the VIA examination which is statistically significant with a P value = 0.223. Vaginal delivery does not always cause cervical injury which is needed by HPV to penetrate the transformation zone which can gradually lead to precancerous lesions or positive VIA results. There is no relationship between history of family planning use and VIA examination results which is statistically significant with p value = 0.994. Women who have never used hormonal or non-hormonal contraception can also experience precancerous lesions or positive VIA examination results.